Issues in the Historical Geography of the Fertile Crescent - Zadok, Ran (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
This article deals with four topics. The first three are about a region and a settlement in Judea as well as a village in Samaria, whereas the fourth is about Hatra in upper Mesopotamia. The discussion of the first topic is the most extensive one. It includes, inter alia, a new mode of microtoponymic classification.